Clinical-Epidemiology Aspect of Inpatients With Moderate or Severe COVID-19 in a Brazilian Macroregion: Disease and Countermeasures - Silva, Bruna Raphaela Oliveira; Rodrigues, Wellington Francisco; Abadia, Daniela Gomes Pires; Alves da Silva, Djalma A.; Andrade e Silva, Leonardo E.; Desidério, Chamberttan S.; Farnesi-de-Assunção, Thais Soares; Costa-Madeira, Juliana C.; Barbosa, Rafaela M.; Bernardes e Borges, Anna V.; Hortolani Cunha, Andrezza C. C.; Pereira, Loren Q.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
COVID-19, also known as coronavirus disease 2019, is an infectious viral disease caused by SARS-CoV-2, a novel coronavirus. Since its emergence, its epidemiology has been explored; however, for some regions of the world, COVID-19’s behavior, incidence, and impact remain unclear. In continental nations like Brazil, this lack of knowledge results in nonuniform control, prevention, and treatment measures, which can be controversial in some locations. This study aimed to describe the epidemiological profile of patients with COVID-19 in the macroregion of Triângulo Sul in the state of Minas Gerais (MG), Brazil. Between March 25 and October 21, 2020, data were collected and statistically analyzed from 395 hospitalized patients in the city of Uberaba, MG, suspected to have moderate or severe forms of the disease. Of the 395 suspected cases, 82% were confirmed to be positive for COVID-19. The mean age of positive patients was 58.4 years, and 60.76% were male. Following these patients throughout their hospitalization, a mortality rate of 31.3% was observed. In the population positive for COVID-19, the risk of death increased by 4% for each year of the patient’s age. Likewise, the older the patient, the longer their hospitalization and the higher the risk of developing acute respiratory failure. Among the treatments tested in patients, heparin was associated with protection against mortality, and the absence of anticoagulant use was linked to a more than six times greater risk of death. Finally, comorbidities in patients with COVID-19 were positively correlated with increased hospitalization time. In summary, this study revealed that age, presence of comorbidities, length of hospitalization, and drug treatment considerably altered COVID-19’s lethality. To understand infection rates and the factors involved in COVID-19’s lethality, knowledge of the local epidemiology is necessary.